Development of Cabatar Learning Media on Flat Geometry Material to Improve Students Numeracy Abilities in Elementary Schools - Anita Lestari; Nurafni Nurafni (Green Publisher Indonesia, 2024)
Coronary Heart Disease (CHD) remains a leading cause of death globally. The accumulation of plaque in the coronary arteries is a primary contributor to CHD. Lipid profiles serve as crucial indicators for assessing risk and monitoring treatment response in CHD patients. This study aimed to analyse the lipid profiles of patients diagnosed with CHD and their association with CHD risk factors such as gender, age, and severity. This quantitative descriptive study was conducted at the Department of Cardiology in the Gatot Soebroto Indonesia Army Central Hospital, Jakarta, Indonesia, from January 2023 to June 2023. Obeying inclusion and exclusion criteria of the study, a total of 84 participants were finalised as the study population. All necessary data were collected, analysed, and disseminated by several programs of MS-Excel and SPSS version 25. Among 84 CHD patients, 66.7% were male and 33.3% were female. On the other hand, over half of the sample (51.2%) was under 60 years old. Results also indicated that 38.6% of patients had one-vessel disease. While a majority of patients had normal levels of triglycerides (64.3%), total cholesterol (64.3%), and HDL (53.6%), a substantial proportion (63.1%) exhibited abnormal LDL levels. In this study, it was found that the majority of CHD patients had high LDL levels and low HDL levels, while triglyceride and total cholesterol levels tended to be normal. This study also discovered that men have lower HDL compared to females with a p-value (<0.05), but there was no difference between age ranges and severity with lipid profiles.